Cardiac safety in vascular access surgery and maintenance - Malik, Jan; Kudlicka, Jaroslav; Tesar, Vladimir; Linhart, Ales (Contributions to nephrology, 2015)
More than 50% of all end-stage renal disease (ESRD) patients die from cardiovascular complications. Among them, heart failure and pulmonary hypertension play a major role, and published studies document significantly higher mortality rates in patients with these two states. Arteriovenous fistulas (AVF) and arteriovenous grafts (AVG) are the preferred types of vascular access (VA). However, both AVF and AVG increase cardiac output and in turn could contribute to (the decompensation of) heart failure or pulmonary hypertension. No really safe access flow volume exists, and the ESRD patients' reactions to it vary considerably. We review the mechanisms involved in the cardiovascular consequences of increased cardiac output and available literary data. The link between access flow volume and increased mortality due to pulmonary hypertension or heart failure probably exists, but still has not been directly evidenced. Regular echocardiography is advisable especially in patients with symptoms or with high VA flow (>1,500 ml/min).
Keywords: echokardiografie; Maintenance; Renal Dialysis; chronické selhání ledvin; Hypertension, Pulmonary; Cardiac Output; dialýza ledvin; údržba; výkony cévní chirurgie; Heart Failure; Hemodynamics; hemodynamika; lidé; srdeční selhání; Arteriovenous Shunt, Surgical; bezpečnost pacientů; Echocardiography; Kidney Failure, Chronic; Vascular Surgical Procedures; cévní přístupy; arteriovenózní zkrat; plicní hypertenze; Patient Safety; Vascular Access Devices; minutový srdeční výdej; Humans